(untitled) (Agroindustria, Sociedad y Ambiente, 2023)
Milk is an essential food in the diet, and in some big cities’ conurbation areas, peri-urban dairy is an important agro-industrial activity. The aim of this work was to establish, employing surveys, the relationship between food security level and socioeconomic characteristics of households in San Salvador Atenco, besides raw milk buying and consumption preferences. The food insecurity level detected was relatively low (11%, 7%, y 3% with mild, moderate, and severe food insecurity levels, respectively), where the scholarly level and the sources of income have a significant relationship with the food security level since lower incomes are related to vulnerability situation. The was no statistical relationship between the kind of milk or the volume consumed and the food security level. The persons feel that raw milk is of better quality, healthier and sustainable, although not so cheap to households with lower income and food insecurity status. The potential of raw milk marketing as a factor de decrease food insecurity is promissory if the necessary support is given to formalize this productive chain toward a sustainable and affordable food production system.